The relationship of wrist and shoulder joint isokinetic strength and service and spike velocity in elite female volleyball players - Aka, H.; Akarcesme, C.; Aktug, Z. B.; Zorlular, A.; Güzel, N. A.; Sökmen, T. (Turkish Journal of Sport and Exercise, 2019)
The purpose of the study was to examine the relationship between isokinetic wrist and shoulder strength and service and spike velocity of the female volleyball players. Totally 34 female volleyball players participated into the study voluntarily. Wrist (60°s-1 and 90°s-1) and shoulder strength (60°s-1 and 180°s-1) of the volleyball players were determined with isokinetic dynamometer; and service and spike velocity was determined with radar device. Pearson Correlation Analysis was performed for determining the relationship between isokinetic wrist and shoulder strength and service and spike velocity of the volleyball players. As result of the statistical analysis, whereas no significant relationship was determined between wrist and shoulder isokinetic strength and service and spike velocities of the female volleyball players (p<0,05), positive significant relationship was found between wrist and shoulder isokinetic strengths (p<0,05). Considering these results, it was possible to mention that although service and spike velocities of the volleyball players were correlational with the upper extremity strength, only wrist or only shoulder strength did not increase the velocity of service and spike, and this appeared by the effect of all upper extremity and bodily muscles. Regarding this, it was considered that volleyball players should develop other variables (strengthening all upper extremity and bodily muscles, improving the technique of spiking, etc.) besides wrist and shoulder strength in order to improve their service and spike velocity.